1984
DOI: 10.1139/m84-096
|View full text |Cite
|
Sign up to set email alerts
|

Acetic, propionic, and oleic acid as the possible factors influencing the predominant residence of some species of Propionibacterium and coagulase-negative Staphylococcus on normal human skin

Abstract: The minimum inhibitory concentration (MIC) of acetic and propionic acid for resident bacteria on normal human skin, such as Propionibacterium acnes and Staphylococcus epidermidis, was 25 mg/mL or more at any pH tested (pH 5.5-6.8). While the MIC of these acids for most of the transient bacteria was markedly decreased by lowering the pH of the media and at pH 5.5, the mean pH value of the normal human skin, the MIC was 6.25 mg/mL or less. The MIC of oleic acid for some strains of Gram-positive transient bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 10 publications
0
41
1
Order By: Relevance
“…The most noticeable growth of inhibition properties were observed in case of propionic acid; lipophilic corynebacteria growth was inhibited at pH 6.0, and at lower pH, some strains of staphylococci did not multiply. These results are partly contrary to the claims of Ushijima et al (1984) that propionic acid is one of the factors determining the dominance on the skin not only of its major producer Propionibacterium spp. but also coagulase-negative staphylococci.…”
Section: Discussioncontrasting
confidence: 99%
“…The most noticeable growth of inhibition properties were observed in case of propionic acid; lipophilic corynebacteria growth was inhibited at pH 6.0, and at lower pH, some strains of staphylococci did not multiply. These results are partly contrary to the claims of Ushijima et al (1984) that propionic acid is one of the factors determining the dominance on the skin not only of its major producer Propionibacterium spp. but also coagulase-negative staphylococci.…”
Section: Discussioncontrasting
confidence: 99%
“…Propionibacterium species are thought to confer health benefits via the production of SCFA. SCFA possess antimicrobial properties and contribute to the acidic pH of the skin in defending against pathogens425253. Disruption in the normal skin pH has been linked to several skin diseases, including atopic dermatitis, ichthyosis, fungal infections54555657, and acne58.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SCFAs exert antimicrobial activities (Ryssel et al 2009; Ushijima et al 1984). Several SCFAs have been approved by the United States Environmental Protection Agency (EPA) as active ingredients for use as fungicides and bactericides on stored grains, poultry litter, and drinking water for poultry and livestock (Sebastian et al 1996).…”
Section: Introductionmentioning
confidence: 99%